THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM PT. HOLCIM INDONESIA TBK CILACAP PLANT ON PUBLIC ATTITUDES IN THE DISTRICT OF SOUTH CILACAP 2014 - Cholifah, Fautia Nurul (Universitas Muhammadiyah Surakarta, 2015)
PT. Holcim Indonesia Tbk Cilacap Plant contributed to society by implementing CSR program Posdaya?. This research aims to analyze the influence of Corporate Social Responsibility (CSR) Program on public attitudes in the District of South Cilacap. This research uses quantitative methods. The samples in this research are 86 respondent recipients in the Posdaya of South Cilacap. The technique of analysis data used a Manova analysis. The result was obtained Manova test is significant level (sigY 1) = 0,000 < 0,05, it means there is significant influence of Corporate Social Responsibility (CSR) on public attitudes. This research shows that there are some factors affect people?s attitudes forms of CSR programs offered to the community such as the training, motivation, and monitoring of the Holcim. So the attitudes of society in the CSR programs have an impact on the participation of the community